Strengthening the gender lens in agricultural production and value-chain research in Vietnam - International Center for Tropical Agriculture (International Center for Tropical Agriculture, 2016)
Farming systems in Vietnam are undergoing rapid change, including increased levels of commercialisation and market integration, adoption of (or desire for) labour efficient technologies, and migration of youth in response to non-farm work opportunities. These processes are not only shaping rural landscapes and communities, but challenging traditional gender roles. ACIAR’s research portfolio seeks to understand underlying trajectories and develop technical and policy innovations to help deliver more productive, sustainable and profitable agricultural systems. Failure to consider gender norms in this process ultimately leads to low levels of adoption of technological innovations and exacerbates gender inequality. As such, gendered roles and differences in access to agricultural knowledge and resources needs to be considered in the design, implementation and evaluation of agricultural research for development to ensure the technologies and policies being evaluated are accessible to women, result in widespread adoption, and leads to the desired impact in terms of improved livelihood.